Polymer of intrinsic microporosity-based macroporous membrane with high thermal stability as a Li-ion battery separator. Issue 37 (10th July 2019) - Tian, Yangyang; Lin, Chong; Wang, Zhenggong; Jin, Jian
Abstract : A PIM-1 macroporous membrane was successfully fabricated and used as a separator of rechargeable Li-ion batteries for the first time. Abstract : Polymers of intrinsic microporosity (PIMs) have numerous advantages such as good thermal stability ( T g > 300 °C) and mechanical stability (tensile strength at break > 60 MPa) as well as excellent electrical insulation performance and chemical/electrochemical stability. Herein, a macroporous membrane made up of a polymer of intrinsic microporosity (PIM-1) was fabricated and used as a separator of a rechargeable Li-ion battery for the first time. The PIM-1-based separator showed good thermal resistance with T g > 300 °C, high electrolyte uptake, and excellent Li-ion conductivity.